Attracting new audiences : attitudes and experiences in attending classical music concert of students in their twenties - Mielonen, Heini (Sibelius-Akatemia, 2003)
The aim of the study was to explore attitudes and experiences of students in their twenties (21-31 years old) in attending classical music concerts. As previous studies show, young people are missing in the audiences of classical music concerts. The majority of the audience members are middle aged, highly educated, of high socio-economical position, women who live in a city. If it is assumed that young people will start to attend when they are older, which has been the case in the past, there is no reason why classical music organisations should be worried: it is enough to wait untill young people get older and they will start to attend concerts. But if young people are not attending because they no longer have same values or life-styles as preceeding generations, the problem is more complicated. Then classical music organisations must face the fact that the total number of audience members might decrease in the future. However, even if it is difficult to predict the changes that will take place in the society in the longer run, it is a challenge for classical music organisations and concert organisers to attract wider audiences to classical music concerts. The object of the study was thus to find out why young university students who could, according to studies, be potential attenders of classical music concerts but are not currently attending. The aim was to study issues that could be thought to influence the attending willingness such as attitudes, experiences, values, life cycle and life-stye related issues. These areas served as a theory part in the study. Also, previous audience research studies were an important source of background information. The method used was a case interview, where seven university students living in Helsinki (20-31 years old) where interviewed before the classical music concert and after the concert. The interview was carried out as a group interview and the participants were asked questions that followed specific themes that were thought to reveal information about their attitudes and experiences. The interview took place at Finlandia Hall. The findings of the study show that there are four principal reasons, why these young people do not attend classical music concerts. Firstly, they are unable to identify themselves with the traditional classical music setting. This setting includes several things such as audience members, venue, music, additional services etc. In fact, this setting is seen to present also the ritual of the classical music concert. This ritual includes unwritten rules that the audience members have to follow in order to be accepted as a member of the community of the classical music audience.Secondly, they cannot fin experiences that they want from attending a leisure time activity, a classical music concert: most important, they don't feel they get entertained by attending classical music concerts. Thirdly, they think that the marketing strategies of the classical music organisations are not adapted to their expectations and the advertisements of classical music concerts do not attract them to attend concerts.The fourth major finding was that young people don't feel they can satisfy their social needs by attending classical music concerts. The purpose of this study was primarily to describe the phenomena of the societal changes and their influence on the classical music concert audiences. However, the major findings of this study could give some new ideas how to better attract younger audience to the concerts. The findings could also help organisers and organisations in using more efficient marketing tools when trying to get young audience. Also, the study discusses the role of the educational programmes in finding young people to the audiences. In the end, there are given some pragmatic improvement ideas for the organisations as well. Key words: young people - music - audience - classical music - Kolb
Keywords: konsertit; yleisö; nuoret aikuiset; taidemusiikki; haastattelututkimus; opiskelijat; fi=taidehallinto|sv=Arts Management|en=Arts Management|